PERAN PENDIDIKAN PROFESI GURU (PPG) DALAM MENINGKATKAN PROFESIONALITAS DAN KUALITAS PEMBELAJARAN DI INDONESIA - Adelia Javiarma; Suci Yuniati; Annisah Kurniati; Depriwana Rahmi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2025)
Teacher Professional Education (PPG) is a strategic programme in improving the competence and professionalism of educators. However, the implementation of PPG still faces various challenges, such as participant readiness, curriculum effectiveness, and its impact on improving the quality of education. Therefore, this study aims to analyse the effectiveness of the PPG program in improving teachers' professional competence. This study used a qualitative method with a descriptive approach. Data were collected through interviews, observation, and document analysis related to the PPG programme. Participants in this study included PPG participant teachers, supervisors, and programme managers. The results showed that the PPG programme contributed significantly to improving teachers' pedagogical and professional competencies, especially in the aspects of lesson planning, teaching strategies, and learner evaluation. However, there are obstacles such as time constraints, high academic load, and lack of synergy between theory and practice in the field. Therefore, improvements are needed in the design and implementation of the PPG programme to make it more adaptive to the needs of teachers and education in Indonesia.